Dopamine systems adaptation during acquisition and consolidation of a skill - Sommer, Wolfgang H.; Costa, Rui M.; Hansson, Anita C. (Frontiers in Integrative Neuroscience, 2014)
The striatum plays a key role in motor learning. Striatal function depends strongly on dopaminergic neurotransmission, but little is known about neuroadaptions of the dopamine system during striatal learning. Using an established task that allows differentiation between acquisition and consolidation of motor learning, we here investigate D1 and D2-like receptor binding and transcriptional levels after initial and long-term training of mice. We found profound reduction in D1 binding within the dorsomedial striatum (DMS) after the first training session on the accelerated rotarod and a progressive reduction in D2-like binding within the dorsolateral striatum (DLS) after extended training. Given that similar phase- and region-specific striatal neuroadaptations have been found also during learning of complex procedural tasks including habit formation and automatic responding, the here observed neurochemical alterations are important for our understanding of neuropsychiatric disorders that show a dysbalance in the function of striatal circuits, such as in addictive behaviours.